Agricultural financing to guarantee food safety in an emerging nation: a case study of Nigeria - Omodero, Cordelia Onyinyechi; Ehikioya, Benjamin Ighodalo (Business: Theory and Practice, 2022)
Investment in agriculture is very crucial in the present situation of Nigeria. The effort to overcome food insecurity can only be efficacious if steps in the right direction will be taken. At this juncture in the Nigerian economic history, the right step to take is to adequately finance agriculture in order to ensure sufficient food production and safety that will save the future of the country. This study emphasizes on investment in agriculture to guarantee food security in Nigeria. Several other studies focus on the numerous challenges food production in Nigeria suffer, however, it is important to come to a conclusion that agriculture requires huge financial investment to thrive. This study examines the impact of agricultural financing and output on food production using data from 2007−2019. The regression result reveals that agricultural output is significant and positive in affecting food production and safety but agricultural financing is immaterial in guaranteeing sufficient food production in the country. This result gives evidence that investment in the agricultural sector will be the solution to food insecurity in Nigeria. The government is by this study encouraged to increase the budget on agriculture in order to boost food supply and safety in the country.